Sociodemographic Factors as Predictors of Cutaneous Eruption Sites in Irritant Contact Dermatitis: An Analytic Study at Dr. Pirngadi Regional Public Hospital - Nathalia E.R. Sipahutar; Joice Sonya Gani Panjaitan; Jenny Ria Sihombing; Hendra Hendra; Suhartomi Suhartomi; Runggu Retno Justiani Napitupulu (International Journal of Public Health Excellence (IJPHE), 2026)
Background: Irritant contact dermatitis (ICD) is a common skin disorder that may be influenced by various sociodemographic factors. These factors are suspected to contribute to the predilection sites of cutaneous eruptions in patients with ICD. Objective: This study aimed to determine the association between sociodemographic factors and the location of cutaneous eruptions in patients with irritant contact dermatitis at Dr. Pirngadi Regional Public Hospital. Methods: This analytic observational study employed a cross-sectional design. A total of 56 ICD patients were included using a total sampling technique. The variables analyzed included sociodemographic characteristics (age, sex, and occupation) as independent variables and eruption sites as the dependent variable. Associations between categorical variables were analyzed using the Chi-square test with the likelihood ratio approach, while the strength of association was assessed using Cramer’s V coefficient. Results: The majority of respondents were female (37; 66.1%), while males accounted for 19 participants (33.9%). Based on occupation, most respondents were housewives (16; 28.6%) followed by civil servants (13; 23.2%). The most common eruption sites were the upper extremities (35.7%) and lower extremities (33.9%). Statistical analysis showed no significant association between age and eruption sites (p = 0.067) or between sex and eruption sites based on the Chi-square likelihood ratio test (p = 0.334; Cramer’s V = 0.243). In contrast, occupation demonstrated a statistically significant association with eruption sites (p = 0.038) with a moderate strength of association according to Cramer’s V (0.504). Conclusion: Occupation is a sociodemographic factor significantly associated with the location of cutaneous eruptions in patients with irritant contact dermatitis.